Assessment of Nurse’s Job Satisfaction in Hemodialysis Units - Mansoor, Luay; Muhammad, Tahseen Rajab (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): This study aimed to assess job satisfaction of nurses’ working in the Haemodialysis centres and to determine the relationship between job satisfaction and their socio-demographic characteristics. Methods: A descriptive design was carried out among nurses working in hemodialysis units in Baquba Teaching Hospital and Baladrooz General Hospital in Diyala Governanate from December 14th, 2022 to March 20th. 2023. A non-probability (purposive) sampling was conductive on 80 nurses. The study’s instrument has two parts: the sociodemographic characteristics of nurses with (8) questions; and the Job Satisfaction Scale for Clinical Nurses (JSS-CN), which has (38) questions. A panel of (12) experts was used to assess the content validity of the questionnaire. Using Pearson Correlations (0.87) for the job satisfaction measure, the validity of the instrument scales was assessed. Data analysis using statistical methods for inferencing and describing the data. Results: The study results showed that two third of the studied nurses (75%), had moderate level of job satisfaction. There was highly statistically significant relation between nurses job satisfaction and their monthly incomes (0.034). Conclusion: The current study concluded that nurses working in hemodialysis units had moderate level of job satisfaction and their monthly income negatively affect their job satisfaction as a nurse in the hemodialysis units. Recommendations: The study recommends health institution to improving the monthly income for nurses and conducting future studies on this subject by taking a sample from a wider group to determine the level of general satisfaction of nurses and its impact on social status.